Báo cáo tiếp thu, giải trình về Kế hoạch tài chính quốc gia và vay, trả nợ công 5 năm giai đoạn 2021-2025 (Số: 27/BC-UBTVQH15) - Ủy ban Thường vụ Quốc hội (2021)
Toàn văn Báo cáo tiếp thu, giải trình về Kế hoạch tài chính quốc gia và vay, trả nợ công 5 năm giai đoạn 2021-2025 (Số: 27/BC-UBTVQH15)